1968
DOI: 10.1051/rnd:19680205
|View full text |Cite
|
Sign up to set email alerts
|

Du Rôle De l'HYPOPHYSE Et Des Ovaires Dans La Biosynthèse Des Œstrogènes Au Cours De La Gestation Chez La Truie

Abstract: On peut conclure que, au cours de la gestation chez la Truie, l'ensemble faeto-placentaire possède les activités enzymatiques nécessaires à la synthèse des oestrogènes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The rapid decrease in oestrogens after parturition suggests that they are produced by the gravid uterus (Fèvre et al, 1968;Robertson & King, 1979) and the negative arterio-venous difference in the uterine and umbilical circulations (Silver et ., 1979) indicates their placental origin. The high oestrogen content of placental tissue (Choong & Raeside, 1974) and the demonstration that fetal placental tissue can convert androstenedione (Ainsworth & Ryan, 1966) or pregnenolone (Craig, 1982) to oestrogens are additional evidence for the placental synthesis of oestrogens in the pig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid decrease in oestrogens after parturition suggests that they are produced by the gravid uterus (Fèvre et al, 1968;Robertson & King, 1979) and the negative arterio-venous difference in the uterine and umbilical circulations (Silver et ., 1979) indicates their placental origin. The high oestrogen content of placental tissue (Choong & Raeside, 1974) and the demonstration that fetal placental tissue can convert androstenedione (Ainsworth & Ryan, 1966) or pregnenolone (Craig, 1982) to oestrogens are additional evidence for the placental synthesis of oestrogens in the pig.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal oestradiol-17ß concentrations have been shown to be lower in gilts carrying small numbers of hypophysectomized fetuses than in those carrying small numbers of normal fetuses (Kendall, Dziuk, Nelson & Thurmon, 1985). The placenta is the major source of oestrogens during gestation in the pig (Fèvre, Léglise & Rombauts, 1968;Robertson & King, 1974) and Craig (1982) showed that the placenta has limited enzymic ability to synthesize oestrogens from pregnenolone by the A4-pathway in vitro. Moreover, the activity of those enzymes essential for the metabolism of progesterone to oestrone increased at term.…”
Section: Introductionmentioning
confidence: 99%
“…The other major group of steroids likely to be affected by inhibition of 3fl-HSD are the oestrogens which are produced by the feto-placental unit in the sow (Fevre, Leglise & Rombauts, 1968;Choong & Raeside, 1974). Oestrone is the predominant oestrogen during late pregnancy in the pig; its concentration rises gradually towards term and is thus associated with the concomitant increase in fetal plasma cortisol (Robertson & King, 1974;Silver et al 1979).…”
Section: General Effects Of Epostane Treatment On Sows Andfetusesmentioning
confidence: 99%
“…Oestrogens, which are luteotrophic in the intact sow (Kidder, Casida & Ruimmer, 1955;Gardner, First & Casida, 1963), are produced by the placenta in this species and increase at Days 25 and 70 (Fèvre, Leglise & Rombauts, 1968 (Goldenberg, Bridson & Köhler, 1972) and stimulate 125I-labelled LH binding to dispersed granulosa cells (Nakano, Akahori, Katayama & Tojo, 1977) and luteal membranes (Garverick, Polge & Flint, 1982) in the sow. Oestrogens also play a role in prolactin receptor regulation, as demonstrated in pig granulosa cells at the time of luteinization (Hammond & Krall, 1979).…”
Section: Sowmentioning
confidence: 99%